External Debt and Economic Growth Nexus in ECOWAS Countries: Moderating Effect of Governance - Adamu Jibir; Stephen Sofah (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
The impact of external debt on economic growth remains a pivotal yet unresolved question for developing economies, particularly in the ECOWAS region. This study argues that the quality of governance is the key to unlocking this puzzle. While external debt can be a catalyst for development, its benefits are often contingent on the institutional environment in which it is managed. To investigate this dynamic, we employ the Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) model—a method chosen for its robustness in handling the statistical challenges of panel data, such as cross-sectional dependence. Our analysis of ECOWAS nations from 2000 to 2023 yields two central findings. First, we confirm a nonlinear relationship, consistent with the Debt Laffer Curve, where moderate debt supports growth, but excessive debt becomes detrimental. Second, and more significantly, we find that governance quality critically moderates this relationship. Strong institutions not only enhance the positive effects of debt but also act as a buffer, mitigating associated risks like macroeconomic instability and exchange rate volatility. Conversely, weak governance exacerbates the downsides of borrowing. These findings underscore that effective debt management is inextricably linked to institutional reform. We therefore contribute to the literature by providing empirical evidence of how governance mechanistically shapes the debt-growth nexus, offering actionable insights for policymakers aiming to harness debt for sustainable development in West Africa.